Cigarette Brand Preference amongst University students in the Greater eThekwini Metropolitan area - Tlapana, T. (IJRDO - Journal of Business Management, 2017)
This article focuses on cigarette brand preference amongst University students in the Greater eThekwini Metropolitan area. Due to the fact that the cigarette industry is now in a maturity stage of the product life cycle, it is important to know the factors which influence cigarettes brand preferences. This research is on cigarette brand preference amongst University students. The research will be done in the KwaZulu Natal Province. It will focus on Universities in the greater eThekwini Metropolitan area. The aims of the study are to identify if brand popularity has any effect cigarette brand preference, to determine if price has any effect, if packaging affects cigarette brand preference and also to analyse the availability of cigarette brands on the university. This research was a quantitative and exploratory in nature. There were 30 respondents who participated. The majority of the respondents (67%) were males and they agreed that brand popularity, price, packaging, availability and motivation had a positive impact towards their brand preference of cigarettes